The Marquis de Sade : a very short introduction - Phillips, John, 1950- (Very short introductions, 2005)
Discussing the 'real' Marquis de Sade from his mythical and demonic reputation, John Phillips examines Sade's life and work his libertine novels, his championing of atheism, and his uniqueness in bringing the body and sex back into philosophy.